Australasian Forensic Science Summit 2016 : business models towards 2030 - Catoggio, Dean; Pearman, Chris (Australian journal of forensic sciences, 2018)
Working group discussion on the characteristics of successful business models for the delivery of forensic science towards 2030 - strengths and risks of current models - analysis of future challenges for forensic science, including changing demand and balancing the needs of policing and criminal justice stakeholders - opportunities for future business models - set of statements developed to stimulate thinking about the future business model needs of forensic science in Australia and New Zealand.